Laser Microdissection and Spatiotemporal Pinoresinol-Lariciresinol Reductase Gene Expression Assign the Cell Layer-Specific Accumulation of Secoisolariciresinol Diglucoside in Flaxseed Coats - Fang, Jingjing; Ramsay, Aïna; Renouard, Sullivan; Hano, Christophe; Lamblin, Frédéric; Chabbert, Brigitte; Mesnard, François; Schneider, Bernd (Frontiers in Plant Science, 2016)
The concentration of secoisolariciresinol diglucoside (SDG) found in flaxseed (Linum usitatissimum L.) is higher than that found in any other plant. It exists in flaxseed coats as an SDG-3-hydroxy-3-methylglutaric acid (HMGA) oligomer complex. A laser microdissection (LMD) method was applied to harvest material from different cell layers of seed coats of mature and developing flaxseed to detect the cell-layer specific localization of SDG in flaxseed; NMR and HPLC were used to identify and quantify SDG in dissected cell layers after alkaline hydrolysis. The obtained results were further confirmed by a standard molecular method. The promoter of one pinoresinol-lariciresinol reductase gene of L. usitatissimum (LuPLR1), which is a key gene involved in SDG biosynthesis, was fused to a β-glucuronidase (GUS) reporter gene, and the spatio-temporal regulation of LuPLR1 gene expression in flaxseed was determined by histochemical and activity assays of GUS. The result showed that SDG was synthesized and accumulated in the parenchymatous cell layer of the outer integument of flaxseed coats.